2015
DOI: 10.1177/1203475415610071
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Serum Level of Vitamin D and Vitiligo

Abstract: There is no difference between the vitamin D levels of the vitiligo patients and the control subjects. However, deficiency of 25(OH)D levels within the vitiligo subgroups may be linked to younger age, male gender, short duration of vitiligo, and non-use of phototherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…Khurrum and AlGhamdi [1] found that there was no difference in vitamin D serum levels between vitiligo patients and controls. The authors added that vitamin D deficiency within vitiligo patients was more manifest in those with younger age, male gender, short disease duration, and lack of phototherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Khurrum and AlGhamdi [1] found that there was no difference in vitamin D serum levels between vitiligo patients and controls. The authors added that vitamin D deficiency within vitiligo patients was more manifest in those with younger age, male gender, short disease duration, and lack of phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The link between vitiligo and vitamin D levels still needs to be investigated more thoroughly. Whether a deficit in vitamin D levels plays a role in inducing vitiligo, as it does in other autoimmune disorders, is not yet clear [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20] There was no significant decrease in vitamin D levels in patients with associated autoimmune comorbidity in our study. Similar results have been found by Khurrum et al, Saleh et al as well as Beheshti et al 7,18,19 All other studies had found a significant decrease in vitamin D levels in patients having comorbid autoimmune conditions. 12-20, Further studies having a larger sample size may reveal a correlation in the Indian context.…”
Section: Discussionmentioning
confidence: 73%
“…Similar results were obtained in a study by Finamor et al as well as Takczi et al 9,11 However the majority of patients in other studies had a mean age below 35. [6][7][8][12][13][14][15][16][17][18][19][20] This may reflect certain social attitudes towards the disease i.e. hesitancy to consult local physicians regarding vitiligo, or presenting to a tertiary center only after prolonged native treatment.…”
Section: Discussionmentioning
confidence: 99%